Charismatic Leadership Effects of Teachers in Fostering Graduate Quality of Senior High School - Dian Widiantari; Muhammad Iqbal Bin Samadi; Abdul Karim (Journal of Leadership in Organizations, 2022)
Introduction/Main Objectives: The purpose of the study is to explore the effects of charismatic leadership teachers in fostering the quality of graduates. Background Problems: Not all teachers establish a close relationship and have an appeal that can affect the learners in the form of thoughts, feelings and behavior in the form of new characters and have the competencies required for entrenched in daily life. Novelty: The importance of developing a closeness teachers and learners emotionally so that the effect on the formation of character and competence of the learners can be achieved. Research Methods: The method used is literature study by analyzing the various articles related to the focus of the research. Data collection use documentation study with the analysis of the data through the data collection, data reduction, and conclusion making. Finding/Results: The results of the study (1) the effect of charismatic leadership can develop a sense of trust and a strong bond between students and teachers without terms for shaping the character of the new positive to be better, (2) learners with a vengeance because of his loyalty dare to do the formation of behavior and increase the competence for the needs of his life in the present and future, (3) motivate learners to have the ideals that are higher and greater ability to achieve these ideals. Conclusion: Teachers who have integrity, hard work, respect and accountability will be emulated by the students as the effect of charismatic leadership.